Adalékok a Horthy-korszak büntető jogtudományának történetéhez - Lehotay, Veronika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
The aim of the study is to demonstrate the arguments and debates of jurists and the experts of the criminology about equality, liberties in the Horthy era when these issues were challenged by the restrictions of rights, such as the Anti-Jewish laws and the racial policies. In this period the criminal law focused on the personality and the social background of the perpetrator as an influence of anthropological criminology which combines the study of human races and their personal characteristics with the criminal propensity instincts. In the literature of criminal law new issues appeared such as the restriction of rights, deprivation of rights and racial policies as the influences of the Nurnberg Laws in the Third Reich. The jurists in Hungary paid close attention to the jurisdiction in the Third Reich, but they did not set an example for Hungary. According to their arguments, the German way of the racial law in the Hungarian context is not adaptable because its society is too multi-ethnic. This resonates with the opinion of Pál Angyal, who was the leading figure of the criminal law in Hungary. According to his view, criminal law cannot be a tool for racism, but it can be useful in the field of civil law and the state administration. Despite the jurist’s cautious argument, the racial policies appeared in legislation after 1938.